Trade operation & settlement process of Haji Ahmad Brothers Securities Limited (HABSL) - Hasib, Hasibul Hasan (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2023.